Bioenergy engineering fundamentals, methods, modelling, and applications - Shadangi, Krushna Prasad (Sawston, England Woodhead Publishing, 2023)
"Bioenergy Engineering: Fundamentals, Methods, Modelling, and Applications presents the fundamental principles, recent developments, innovative state-of the-art technologies, challenges, solutions and future perspectives on the production of biofuels and bioenergy. Balancing the scientific and engineering aspects of biofuels production, the book guides readers through the chemical kinetics, modeling, thermodynamics, unit operations and technological advancements in fuel processing from conventional and alternative resources. Each chapter of the book starts with the fundamentals and goes on to assess the latest technologies for the production of renewable fuels on topics.

Sections cover biomass utilization, biomass-to-liquid conversion technologies (pyrolysis, liquefaction, solid-state fermentation and submerged fermentation), biomass-to-gas conversion technologies (thermochemical gasification, subcritical and supercritical water gasification, and methanation), gas-to-liquid conversion technologies (Fischer-Tropsch synthesis), carbonization, transesterification, organic transformation, carbon-carbon and carbon-heteroatom coupling reactions, oxidation, reforming, hydrotreating technologies (hydrogenation, hydrodesulfurization, hydrodenitrogenation, hydro dearomatization and hydro demetalization), nanocatalysis and biocatalysis (enzymatic hydrolysis), and much more."
Includes bibliographical references and index.
Keywords: Biomass energy; Renewable energy sources; Fuel -- Technological innovations